Potensi Pengembangan Budidaya Jamur Tiram Bagi Kelompok Tani Di Sekitar Hutan Pendidikan Universitas Hasanuddin - Ira Taskirawati; Baharuddin Baharuddin; Syahidah Syahidah; Sitti Nuraeni; A Agussalim; Beta Putranto; S Suhasman; Andi Detti Yunianti (Repong Damar: Jurnal Pengabdian Kehutanan dan Lingkungan, 2022)
Guidance for community groups around the Unhas Education Forest needs to be carried out to encourage increased public awareness about the importance of preserving the forest without losing its benefits of the forest. Furthermore, the community can use the number of visits, both individually and in groups, to the Unhas educational forest for various purposes as a market opportunity to increase income. One of the commodities cultivated by the local community is the oyster mushroom (Pleurotus ostreatus). Overall, this community service activity is carried out through a series of activities, including lectures, focus group discussions, training and demonstrations, and workshops. This activity is expected to make the community feel the benefits of the forest and play an active role in conserving the forest. In addition, it can improve the welfare of the people living around the forest. The activity results showed that after participating in the training, 75 per cent of the participants were able to explain the stages of mushroom cultivation.